Optimization of Anti-ssDNA Antibody Purification: A Comparative Study in SLE Patients - Anna Kats; Mirjana Pavlovic; Ran Chen; Michelle Cavallo; James X. Hartmann (Recent Developments in Chemistry and Biochemistry Research Vol. 10, 2025)
Background: The hallmark of systemic lupus erythematosus (SLE) is the production of an array of IgG and IgM auto-antibodies directed against one or more nuclear components, most commonly double-stranded (ds) DNA and/or single-stranded (ss) DNA. Both anti-ssDNA and anti-dsDNA antibodies are considered to be involved in disease development based on the fact that both have been eluted from the kidneys of experimental murine models and SLE patients. Purpose: A two-step affinity purification method was compared, previously developed in-house, which utilizes biotinylated oligo-deoxythymidine (dT) bound streptavidin (SA) M-280 magnetic beads and protein G Dynabeads®, with Melon™ Gel, another two-step commercial method, for the isolation and purification of human anti-DNA autoantibodies reactive with single-stranded DNA (ssDNA), to determine which method is more applicable for analysis of antibody subclasses and, potentially subclass functional activities. Methodology: Whole blood was intravenously drawn with written consent and under the guidance of protocols approved by the Florida Atlantic University’s Institutional Review Board. To perform an IEF analysis, the samples of purified antibodies were applied to a gel (polyacrylamide) with the electric current applied to create migration using the Pharmacia PhastSystemTM and PhastGelTM IEF Gradient 3-9 separation gels, PhastGelTM buffer strips, and full-range rainbow molecular weight markers. Moreover, Western blot was used to determine the identity of an electrophoretically separated protein and to measure relative amounts of the protein present in different samples, based on densitometry. Results: Although Melon Gel allowed for faster anti-ssDNA autoantibody purification and higher recovery rate, its final product was of lower purity than that of the magnetic bead method, as confirmed with the nanogram silver staining method following PhastGelTM non-reducing SDS-PAGE. The polyclonal nature of anti-ssDNA autoantibodies produced by patients with Systemic Lupus Erythematosus (SLE) has been determined and compared with normal human, and B-Chronic Lymphocytic Leucosis- (B-CLL) anti-ssDNA autoantibodies. Analysis of isolated antibodies by isoelectric focusing, western blot analysis and ELISA confirmed them to be human IgGs and detected the presence of all four IgG antibody subclasses with different participation. Additionally, the Lab-on-chip (Agilent 2100) method revealed the presence of different MW patterns within lupus IgG subclasses, not detectable by SDS PAGE, which were not consistent with patterns seen in sera of control or individuals with B-CLL. Conclusions: The results obtained suggest incomparably better purity of antibodies isolated via the magnetic bead method vs. Melon-gel. SDS-PAGE and Lab-on-chip analyses of antibodies revealed the presence of different IgG patterns within human lupus anti-ssDNA autoantibody subclasses than those observed in healthy individuals and B-CLL patients. The reason for different structural patterns of anti-ssDNA autoantibodies in SLE could be the product of genetic and epigenetic changes. Activation of mutated genes and alternative epigenetic mechanisms can be involved in the production of pathogenic anti-DNA antibodies. These patterns may be associated with SLE disease pathogenesis and highlight the importance of further molecular, structural, and functional studies of lupus anti-ssDNA antibodies.